Strategi Pengembangan Wisata Religi Dalam Peningkatan Perekonomian Masyarakat Sekitar Masjid Tegalsari Ponorogo - Ulfihawin Mawadah; Maulida Nurhidayati (Niqosiya: Journal of Economics and Business Research, 2024)
This research is motivated by problems in development strategy. Several obstacles exist in Tegalsari religious tourism. The community's economic involvement is not only limited to consumers but also to business actors in the shophouses that have been provided. This research uses descriptive qualitative qualitative research methods to analyze religious tourism development strategies, the impact of development strategies, supporting factors, and inhibiting factors. Data collection techniques are carried out through interviews, observation, and documentation. In this research, we looked at the trustworthiness of triangulating sources. The development strategy carried out by the Tegalsari Ponorogo Jami Mosque religious tourism has implemented a SWOT analysis, although several weaknesses need to be corrected. The positive impact of religious tourism in Tegalsari Ponorogo is that income from business is helped employment, and utilization of tourism facilities by the local community. The negative impact is too much dependence on tourism and seasonal tourism activities. Supporting factors for Tegalsari religious tourism are related to visitor attraction because there is the tomb of Kyai Ageng Muhammad Besari, support from the government, good security, and a tourist attraction atmosphere that provides comfort. The inhibiting factors are limited parking space when there are many visitors, lack of awareness of environmental cleanliness, and lack of street lighting.